2015
DOI: 10.1038/leu.2015.306
|View full text |Cite
|
Sign up to set email alerts
|

Azacitidine in combination with intensive induction chemotherapy in older patients with acute myeloid leukemia: The AML-AZA trial of the study alliance leukemia

Abstract: DNA methylation changes are a constant feature of acute myeloid leukemia. Hypomethylating drugs such as azacitidine are active in acute myeloid leukemia (AML) as monotherapy. Azacitidine monotherapy is not curative. The AML-AZA trial tested the hypothesis that DNA methyltransferase inhibitors such as azacitidine can improve chemotherapy outcome in AML. This randomized, controlled trial compared the efficacy of azacitidine applied before each cycle of intensive chemotherapy with chemotherapy alone in older pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…For the combination subgroup analysis, Studies using standard dose of intensive chemotherapy (DA, IA, etc.) [17][18][19][20] were classified as HMA + high-intensity subgroup, while those using reduced dose of intensive chemotherapy [21][22][23] were taken as HMA + low-intensity subgroup. Studies with compatible age and cytogenetic risk were first selected according to the median age.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the combination subgroup analysis, Studies using standard dose of intensive chemotherapy (DA, IA, etc.) [17][18][19][20] were classified as HMA + high-intensity subgroup, while those using reduced dose of intensive chemotherapy [21][22][23] were taken as HMA + low-intensity subgroup. Studies with compatible age and cytogenetic risk were first selected according to the median age.…”
Section: Study Selectionmentioning
confidence: 99%
“…Among them, studies of compatible age and proportion of favorable/intermediate cytogenetic risk were further screened, and six studies were selected as candidates. After excluding one study [24] in monotherapy group with a high proportion of patients receiving HSCT and a consequent deviation in OS, five studies (Müller-Tidow et al, Li et al and Krug et al's study on combination therapy [19,20,23], and van der Helm et al and Fenaux et al's study on monotherapy [9,25]) were selected for subgroup analysis, and adding any other study to either subgroup would lead to a significant difference in either pooled estimate of age or proportion of cytogenetic risk. Same strategy was used for selecting studies with compatible baseline characteristics in high or low-intensity of chemotherapy + HMA subgroups, and only Krug et al and Li et al's study [20,23] were selected and analyzed.…”
Section: Study Selectionmentioning
confidence: 99%
“…Additionally, data from a clinical phase 1 study analyzing a combination of decitabine with standard induction chemotherapy suggested its use to be safe and feasible [99]. Unfortunately, however, the authors of a large and randomized phase II trial, who studied the combination of azacitidine and standard induction chemotherapy in older AML patients, failed to observe a beneficial effect of this regimen [100]. It will be interesting to see, whether these results can be ameliorated by altered dosing schedules or by the use of newer hypomethylating agents, such as guadecitabine [101].…”
Section: Mirnas and Lncrnas In Sensitivity And Resistance To Low-imentioning
confidence: 99%
“…[78] Randomized comparison of 3 1 7 followed by high dose cytarabine each 1/-azacitidine has not demonstrated differences in survival or EFS. [79]. Newer formulations that provide longer exposure (oral azacitidine, guadecitabine) [80] are under investigation as are increases in duration of decitabine from 5 to 10 days or azacitidine from 7 to 10 days [78].…”
Section: Annual Clinical Updates In Hematological Malignanciesmentioning
confidence: 99%